2013
DOI: 10.2166/wp.2013.006
|View full text |Cite
|
Sign up to set email alerts
|

Ten fundamental questions for water resources development in the Ganges: myths and realities

Abstract: This paper summarizes the results of the Ganges Strategic Basin Assessment (SBA), a 3-year, multi-disciplinary effort undertaken by a World Bank team in cooperation with several leading regional research institutions in South Asia. It begins to fill a crucial knowledge gap, providing an initial integrated systems perspective on the major water resources planning issues facing the Ganges basin today, including some of the most important infrastructure options that have been proposed for future development. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Flow, sediment, and nutrient fluxes can provide critical information that can assist the Indian and Bangladesh governments to mitigate future impacts. There are several existing modelling studies on the Ganges river, most of which were funded by either government departments or international organisations, such as the World Bank (Sadoff et al 2013). In order to undertake an assessment of the hydrology and nutrient dynamics in the GBM rivers, the semi-distributed, process-based INCA model (INtegrated Catchment model) for nitrates (N) and phosphates (P) is applied to the whole of the GBM river systems (Whitehead et al 2015a, b).…”
Section: Gbm River Studymentioning
confidence: 99%
“…Flow, sediment, and nutrient fluxes can provide critical information that can assist the Indian and Bangladesh governments to mitigate future impacts. There are several existing modelling studies on the Ganges river, most of which were funded by either government departments or international organisations, such as the World Bank (Sadoff et al 2013). In order to undertake an assessment of the hydrology and nutrient dynamics in the GBM rivers, the semi-distributed, process-based INCA model (INtegrated Catchment model) for nitrates (N) and phosphates (P) is applied to the whole of the GBM river systems (Whitehead et al 2015a, b).…”
Section: Gbm River Studymentioning
confidence: 99%
“…In recent years, World Bank-funded activities under South Asian Water Initiative attempt to develop knowledge as well as networks between countries and stakeholders in multiple basins of the South Asian region (see, e.g. Sadoff et al 2013)(World Bank 2014). An underlying challenge for sustainability is that both Nepali and Indian hydrocracies subscribe to the view of utilising the river to maximise its economic benefits (Mirumachi 2015: 71-73).…”
Section: Static Arrangements On the Gangesmentioning
confidence: 99%
“…Popular belief is that having large dams is the only option to meet the basin's water storage needs (Onta, 2001). However, contrary to that, the Ganges strategic basin assessment conducted by the World Bank (2012) found that the sustainable use of the basin's vast groundwater aquifers can store far greater volumes of water compared to the potential of man-made storage in the basin, which is about 130-145 billion m 3 (Sadoff et al, 2013). For instance, the mean annual replenishable groundwater in the Ganges basin is about 202.5 billion m 3 (Ministry of water resources, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…The major causes of floods in the downstream areas are the shallow groundwater table and high monsoonal rainfall in these areas, and the large runoff generated in the upstream sub-basins. Previous studies (Revelle and Lakshminarayana, 1975;Sadoff et al, 2013) indicated that, due to the limitation of the construction of large surface reservoirs, recharging groundwater beyond the natural level is the best way to control floods downstream. Subsurface storage (SSS) also allows one to meet water requirements during the dry months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation